Investigating the Effect of Intercultural Communication Apprehension on Intercultural Willingness to Communicate with Structural Equation Modeling - Ömer Faruk Koçak (Selçuk Üniversitesi Sosyal Bilimler Enstitüsü Dergisi)
Intercultural communication anxiety is expressed as fear or anxiety associated with communicative actions established or planned to be established with groups of different cultures and ethnicities. This anxiety, which can manifest itself in the education processes of international students, who are important actors of intercultural communication, can negatively affect the willingness of students to communicate with other ethnic groups. The purpose of this study is to demonstrate the effect of international students' intercultural communication apprehension on intercultural willingness to communicate with a proposed research model. 290 (164 male, 126 female) international students studying in Kayseri participated in the research. Structural equation model was used in data analysis in this study, in which data were collected by questionnaire method. As a result of the analysis, the proposed research model was confirmed. As a result of the research, it has been determined that intercultural communication apprehension has a negative effect on the intercultural willingness to communicate